Ways of achieving fault tolerance of heterogeneous information systems under conditions of external influence - Frolov, D. Y. (ХНУРЕ, 2024)
The concept of fault tolerance in relation to the functioning of information systems is the key indicator of reliability. As a rule, classical information systems that can be described using tuple mathematics are rare. Instead, in practice, heterogeneous information systems are created. They have properties of other systems, including technical.
Keywords: fault tolerance; heterogeneous information systems